2015
DOI: 10.1089/wound.2014.0579
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chemokines in Mesenchymal Stem Cell Homing to Wounds

Abstract: Significance: Mesenchymal stem cells (MSCs) are being administered to cutaneous wounds with the goal of accelerating wound closure and promoting regeneration instead of scar formation. An ongoing challenge for cell-based therapies is achieving effective and optimal targeted delivery and engraftment at the site of injury. Contributing to this challenge is our incomplete understanding of endogenous MSC homing to sites of injury. Recent Advances: Chemokines and their receptors are now recognized as important medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 49 publications
4
116
0
2
Order By: Relevance
“…An example for co-existing immobilized and soluble chemokine gradients is the mobilization of mesenchymal stem cells during tissue regeneration by soluble chemokines such as CCL19 on the one side and chemokines that bind to extracellular glycosaminoglycans such as CCL2, CXCL12 or CCL5 on the other side2627. Also, guided cell migration presumably mediated by chemotactic and haptotactic signals are of importance in the pathogenesis of autoimmune diseases such as multiple sclerosis (MS)28.…”
Section: Resultsmentioning
confidence: 99%
“…An example for co-existing immobilized and soluble chemokine gradients is the mobilization of mesenchymal stem cells during tissue regeneration by soluble chemokines such as CCL19 on the one side and chemokines that bind to extracellular glycosaminoglycans such as CCL2, CXCL12 or CCL5 on the other side2627. Also, guided cell migration presumably mediated by chemotactic and haptotactic signals are of importance in the pathogenesis of autoimmune diseases such as multiple sclerosis (MS)28.…”
Section: Resultsmentioning
confidence: 99%
“…The site of injury could be exuding signals that are recognized by the injected stem cells, which prompts them to attach to the blood vessel wall, which then stimulates the angiopellosis process to occur. Chemokines and their receptors have been reported as important mediators in the process of stem cell homing . Another possibility is that signals on the injected cell's membrane are interacting with the receptors on the blood vessel endothelial cells, asking for the cells removal from the lumen.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that MSCs have relatively weak homing ability [27,28]: the major reason is that the expression of CXCR4, the primary receptor for main chemokine (stromal cell-derived factor 1; SDF1), is not high on the surface of MSCs, especially in long-term expansion culture [27e31]. Therefore, many studies have reported on enhancement of the homing ability of MSCs through the increase of CXCR4 expression by viral In this study, CXCR4 gene was overexpressed in mBM-MSCs by minicircle microporation, and the resulting improvement of homing ability was confirmed by in vivo bioluminescence imaging.…”
Section: Overexpression Of Cxcr4 For Enhanced Migration Of Mscs Towarmentioning
confidence: 99%